Parenteral nutrition extravasation associated liver injury - A case series with varying clinical-radiological presentations - Viraraghavan Vadakkencherry Ramaswamy; Gajanan Venkat Rao; Nori Suryanarayana; Sanghamitra Gummadapu (Hygeia Press di Corridori Marinella, 2019)
Umbilical vein catheterisation is a very common procedure in Neonatal Intensive Care Units. The tip of the umbilical vein catheter (UVC) should be located at the junction of inferior vena cava and right atrium, which is confirmed by an abdominal radiography or ultrasonography. The tip of the UVC can migrate to a different position because of a myriad of reasons. If hypertonic solutions are infused through an UVC which is malpositioned in the liver, it can result in serious complications. This is a case series of three neonates with malpositioned UVC and the resultant clinical presentations along with the characteristic ultrasonographic findings.